Embedded Electromechanical Impedance and Strain Sensors for Health Monitoring of a Concrete Bridge - Dansheng Wang; Junbing Zhang; Hongping Zhu (Shock and Vibration)
Piezoelectric lead zirconate titanate (PZT) is one of the piezoelectric smart materials, which has direct and converse piezoelectric effects and can serve as an active electromechanical impedance (EMI) sensor. The design and fabrication processes of EMI sensors embedded into concrete structures are presented briefly. Subsequently, finite element modeling and modal analysis of a continuous rigid frame bridge are implemented by using ANSYS and MIDAS and validated by the field test results. Uppermost, a health monitoring technique by employing the embedded EMI and strain sensors is proposed in this paper. The technique is not based on any physical model and is sensitive to incipient structural changes for its high frequency characteristics. A practical study on health monitoring of the continuous rigid frame bridge is implemented based on the EMI and strain signatures. In this study, some EMI and strain sensors are embedded into the box-sectional girders. The electrical admittances of distributed EMI active sensors and the strains of concrete are measured when the bridge is under construction or in operation. Based on the electrical admittance and strain measurements, the health statuses of the continuous rigid frame bridge are monitored and evaluated successfully in the construction and operation stages using a root-mean-square deviation (RMSD) index.